Peningkatan Kualitas hidup Ibu-Ibu PKK Melalui Penerapan Pola Hidup Sehat Dikecamatan Sariwangi - Resty Agustryani; Selly Purnama; Novi Soraya; Nida Wahyu (Lembaga Pengembangan Kinerja Dosen, 2025)
The current era is an era of scientific and technological progress which gives rise to competition in various fields as well as socio-economic improvements which have an impact on the level of public health and life expectancy, so that the number of people who pay less attention to health is also increasing. The most important impacts are physical, psychological and social setbacks. Mothers are one of the efforts to maintain health nowadays because mothers play a greater role in maintaining family health and need to understand balanced nutritional intake and a healthy lifestyle. From a survey conducted by the service team through interviews with several residents, it is known that the high population of mothers in Sariwangi village is a concern for the community, but the problem is related to the health of mothers. This service was carried out at the PKK Selawangi Village and Posyandu Cempaka 3 Selawangi Village, Sariwangi District. The first stage is planning the activities carried out. The second stage is the implementation of service activities in the form of solutions that have been approved by partner 1 and partner 2, namely Sariwangi Village.